Why Does Risk Matter More in Recessions than in Expansions? - Martin M. Andreasen; Giovanni Caggiano; Efrem Castelnuovo; Giovanni Pellegrino (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper uses a nonlinear vector autoregression and a non-recursive identification strategy to show that an equal-sized uncertainty shock generates a larger contraction in real activity when growth is low (as in recessions) than when growth is high (as in expansions). An estimated New Keynesian model with recursive preferences and approximated to third order around its risky steady state replicates these state-dependent responses. The key mechanism behind this result is that firms display a stronger upward nominal pricing bias in recessions than in expansions, because recessions imply higher inflation volatility and higher marginal utility of consumption than expansions.
Keywords: C32; E32; 330; New Keynesian model; nonlinear SVAR; non-recursive identification; state-dependent uncertainty shock; risky steady state